The 8% solution: preventing serious, repeat juvenile crime - Schumacher, Michael Allen (Sage Publications, 2000)
The 8% problem -- Crime at an early age -- Disrupted families -- School failure -- Drug and alcohol abuse -- Gangs, runaways, and thieves -- Laying the groundwork -- From the ivory tower to the street -- All's well that ends well -- A case study -- The 8% solution--Orange County style -- Overcoming barriers -- The future of the 8% solution